Lactogenic effects of the leaf’s powder of Spondias mombin L. on West African Dwarf (WAD) sheep performance and serum prolactin level in Republic of Benin - akouedegni, guénolé; Adenile, Adam; Olounlade, Pascal (My University, 2020)
Twenty four (24) dairy ewes at the 4th stage of lactation were used to assess the milk production and serum prolactin level of ewes treated with leaf’s powder of Spondias mombin. The lactating ewes were selected and divided into 4 groups of 6 ewes per group: control group (no fed powder of Spondias mombin), Galactin group (no fed powder of Spondias mombin but treated with lactogenic drug) and groups treated with powder of Spondias mombin (group single dose and group double dose). The parameters measured include daily milk production, body weight of lambs and ewes. The resulted outcomes indicate that ewes that received powder of S. mombin and Galactin produced more milk than controls. The average daily increases in milk production were 9.92%, 14.25% and 18.88% in single dose, double dose and Galactin groups, respectively compared to control group. Lamb weight gain was also significantly higher than that in the control group. The treatments did not influence body weight of ewe. The daily weight gain of 93.12; 97.47; 99.07; 86.76 g/day were found in single dose, double dose, Galactin and control groups, respectively. The results of the blood analysis of hormone showed that serum prolactin levels increased in the group treated with powder and Galactin compared to control group.
Keywords: Lactogenic plant; Milk production; Republic of Benin; Sheep; Spondias mombin.